KESESUAIAN BIDANG PENDIDIKAN TERHADAP KEGIATAN PEMBELAJARAN DI SEKOLAH DASAR - Limsi, Limsi; Iswatiningsih, Daroe (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
The alignment between educational fields and learning activities in Elementary Schools is very important in creating effective and enjoyable learning experiences for students. This study aims to analyze how the implemented curriculum is in line with the needs and characteristics of students at the elementary level. Through a qualitative approach, data were collected through observation, interviews, and analysis of curriculum documents. The results of the study indicate that there is a gap between the expected educational theory and classroom learning practices. Factors such as limited resources, lack of teacher training, and parental support affect the effectiveness of learning activities. Therefore, it is recommended that schools and policy makers conduct continuous evaluation and improvement of the curriculum and teaching methods to ensure that learning activities are in line with broader educational goals.